Enhancing phosphorus uptake and yield of wheat with phosphoric acid application in calcareous soil. (13th September 2016) - Hashmi, Zafar Ul Haq; Khan, Muhammad Jamal; Akhtar, Muhammad; Sarwar, Tahir; Khan, Mohammad Jamal
Abstract: BACKGROUND: Low phosphorus (P) availability to wheat from commercial fertilizers is one of the reasons for lower grain yield and hence justifies search for more efficient P source under alkaline calcareous soils. RESULTS: Phosphoric acid (PA) and diammonium phosphate (DAP), applied through conventional and modified methods, were assessed for P supply and wheat yield in a calcareous soil. Under laboratory conditions, pre‐incubated soil with 70 mg P kg −1 soil as PA and DAP was assessed for solution P ( C p ) for 4 weeks. Phosphorus sorption data were fitted using the Freundlich model for describing analyzed sorption in soil incubated with or without DAP and PA. The fitted model equations exhibited comparatively higher effluxes of P from the solution system in control treatment. Compared to DAP, lower quantities (19.6%) of P for PA‐treated soil were required for producing optimum P concentration in soil solution, i.e. 0.2 mg P L −1 . The greenhouse study involved 32 P tracer technique to quantify the proportion of applied P derived by wheat from fertilizer or soil. The results showed that P derived from fertilizer was highest (47.5%) in PA placement, while the lowest (31.5%) was in DAP broadcast treatment. The field study also showed similar trends to that of the greenhouse study. The PA placement treatment resulted in highest (23.4%) phosphorus use efficiency, whereas the lowest one (17.1%) was recorded for DAP broadcast treatment. CONCLUSION: PA proved to be a better P source than DAP for improving P content and achieving higher yield and recovery of applied P by wheat grown in alkaline calcareous soils. © 2016 Society of Chemical Industry